The Critical Linkage between Online and Offline Media: An Approach to Researching the Conditions of Issue Spill-over - Pfetsch, Barbara; Adam, Silke; W. Bennett, Lance (Javnost-The Public, 2013)
In this article we argue that it is pressing to study the “hybrid media system” at the intersection of online and offline communication and its potential for agenda building. The topic is relevant because it is argued that the internet offers new opportunities of public influence for challengers without access to political decision making. Except for single case studies, little is known about the conditions under which these actors succeed. Informed by the research on agenda building we tackle with the mechanisms of online-offline media agenda building and the conditions under which challengers succeed to produce issue spill-over into conventional mass media. We develop a theoretical framework for investigating the linkage between online communication and traditional mass media and discuss how our model translates into empirical research. We conclude that the nature of online networks is critical for spill-over, but also the issue itself and the structure of the political system.